World Bank and Multi-donor trust fund investment for social protection and economic resilience in Mozambique (USD 167M): Influencing the design of the project - CGIAR Research Program on Policies, Institutions, and Markets (2021)
PIM findings on how to design safety nets to decrease intimate partner violence informed the design of the Social Protection and Resilience Project in Mozambique.